A DREaMR system to simplify combining mutations with rescue transgenes in Aedes aegypti. Issue 3 (10th September 2021) - Chen, Jieyan; Luo, Junjie; Gurav, Adishthi S; Chen, Zijing; Wang, Yijin; Montell, Craig
Abstract: In most experimental animals, it is challenging to combine mutations and rescue transgenes and to use bipartite systems to assess gene expression. To circumvent the difficulties in combining multiple genetic elements, we developed the DREaMR ( D rug-on, RE porter, M utant, R escue ) system. Using Drosophila white as the initial model, we demonstrated that introduction of a single insertion by CRISPR/Cas9 created a null mutation, a tagged rescue construct, which could be induced with doxycycline, and which allowed assessment of protein expression. To create a DREaMR in an organism in which combining multiple genetic elements is more problematic than in Drosophila, we tested the mosquito, Aedes aegypti —the insect vector for dengue, yellow fever, Zika, and other viral diseases. We generated a DREaMR allele in the kh gene, which permitted us to induce expression of the rescue construct, and detect expression of Kh. Thus, this system avoids the need to perform genetic crosses to introduce an inducible rescue transgene in a mutant background, or to combine driver and reporter lines to examine expression of the targeted protein. We propose that DREaMR provides a system that can be applied to additional mosquito vectors as well as other organisms in which CRISPR/Cas9 is effective. Abstract : Chen, Luo, Gurav et al . present the DREaMR ( D rug-on, RE porter, M utant, R escue ) system for combining a mutation, a rescue transgene, and to assess gene expression using a single insertion in the endogenous gene. They demonstrate the effectiveness of the DREaMR system using the Drosophila white and Aedes kh genes. The authors suggest that the DREaMR system can be used in other organisms in which it is possible to employ CRISPR/Cas9.